A frequency mapping method for locating functional units inside ICs based on coaxial microscope. Issue 3 (18th November 2021) - Liu, Pengcheng; Han, Jianwei; Ma, Yingqi; Zhang, Feng; Wu, Zongguo; Zhu, Xiang; Cui, Yixin
Abstract: Locating the physical position of functional units of the chip is a mandatory first step in various fields of applications, such as reverse engineering and hardware security. This paper presents a frequency mapping method based on the coaxial microscope to locate functional units inside ICs. A visible light camera is employed to focus the laser on the active region of the device under test based on the principle that the laser is strongly reflected at the metal in the active region. The target circuit modulates the laser at its operating frequency and the position of the target circuit could be accurately located by analyzing the frequency characteristics of the reflected laser. The results of transceiver chip localization indicate that the target circuit on the chip can be precisely located by this method without any additional processing of the chip. The coaxial microscopy design provides a good spot quality and signal‐to‐noise ratio, meanwhile, locating areas of the chip with operating currents down to 10 −10 A, compared with that of photonic emission analysis can only achieve the sensitivity of 5 × 10 −4 A. The sensitivity of the frequency mapping method is much better than that of Photonic Emission Analysis.